The Rare Presentation of Traumatic Intracranial Hypotension: A Case Report - Senapati, Satya Bhusan; Acharya, Abhijit; Mohanty, Ranjan Kumar; Puppala, Sumirini (Asian Journal of Neurosurgery, 2025)
Cerebrospinal fluid (CSF) provides buoyant support to the brain and spinal cord. According to the Monroe-Kellie doctrine, confined space in the cranium causes any change in CSF volume contributing to significant intracranial pressure changes, which cause a variety of pathologies and symptoms. We, hereby, present a case of a 33-year-old gentleman who after a motorcycle road traffic accident came to us complaining of persistent headache and neck pain with subdural hematoma (SDH) like presentation, clinically and radiologically, but was reevaluated and diagnosed as traumatic intracranial hypotension and successfully managed surgically after that. Hygromas are believed to be compensatory enlargement of the subdural space due to the loss of CSF volume. The true mechanism of the development of SDH or hygroma due to intracranial hypotension is yet to be hypothesized but provisionally described by a rupture of the bridging veins by being pulled away from the dura because of the low intracranial pressure (ICP) and brain descent. Many prior cases in the literature are shown to have treated the patient with immediate burr hole and decompression of SDH, but this paradoxically worsens the patient due to further lowering of ICP. The causes of prolonged postconcussion headaches are often unidentified, of which intracranial hypotension caused by a CSF leak is potentially under-recognized. In such cases, bilateral SDH with mass effect must be ruled out of any CSF leak before attempting the lifesaving decompressive surgery, as it may paradoxically lead to further morbidity and mortality of the patient.
Keywords: cerebral contusion; headache; hygroma; intracranial hypotension; SDH; traumatic IH